Phytohormonal responses in enod40-overexpressing plants of Medicago truncatula and rice - Dey, Moul; Complainville, Arnaud; Charon, Celine; Torrizo, Lina; Kondorosi, Adam; Crespi, Martin; Datta, Swapan (Wiley, 2004)
Phytohormones are well‐known regulators of the symbiotic Rhizobium–legume association in the plant host. The enod40 nodulin gene is associated with the earliest phases of the nodule organogenesis programme in the legume host and modifying its expression resulted in perturbations of nodule development in Medicago truncatula. Therefore in our pursuit to mimic the initial signal transduction steps of legume nodulation in the alien physiological set‐up of a rice plant, we have expressed the Mtenod40 gene in rice. Molecular data confirm the stable integration, inheritance and transcription of the foreign gene in this non‐legume. We have compared the phytohormonal responses of Mtenod40‐overexpressing and control plants in a homologous legume background (M. truncatula) and in the non‐legume rice. An enod40‐mediated root growth response, induced by inhibition of ethylene biosynthesis, was observed in both plants. On the other hand, a significant differential effect of cytokinins was observed only in rice plants. This suggests that ethylene inhibits enod40 action both in legumes and non‐legumes and reinforces that some of the early signal transduction steps of the nodule developmental programme may function in rice.